نطاق الرقابة القضائية على تصرفات الإدارة - جفالي, أسامة (Revue jurisprudence, 2018)
إنطلاقا من فكرة أنّ القاضي الإداري هو حامي الحقوق والحريّات الأساسيّة، فإنّ الرّقابة التّي يمارسها هذا الأخير على نشاط الإدارة لم تعدّ تلك الرّقابة التّقليدية التّي تستبعد من اختصاصها الكثير من التّصرفات الإداريّة، بل أصبحت تشمل كلّ أنواع العمل الإداري بما في ذلك التّصرفات المحصنة بمقتضى النّصوص القانونيّة، بل حتى القرارات التّنظيمية أصبحت هي الأخرى عرضة للرّقابة القضائية عن طريق الدفع بعدم مشروعيّتها، زد على ذلك، فإن الإختصاصات الرقابية للقاضي الإداري إمتدّت أيضا إلى فحص مدى ملائمة التّصرفات الإدارية، التّي كانت إلى وقت قريب خطوطا حمراء بالنسبة للقاضي الإداري، فظهرت بذلك الكثير من النظريات القضائية التي تجيز وتبرر الرقابة القضائية على السلطة التقديرية للإدارة. الكلمات المفتاحية: القاضي الإداري. الرقابة القضائية. المشروعية . الملائمة. الإدارة   Abstract : Based on the idea that the administrative judge is the guardian of fundamental rights and freedoms, the latter's control over the activity of the administration is no longer the traditional control, which excludes from its jurisdiction a lot of administrative behavior, but it includes all kinds of administrative work, including acts protected by legal provisions , And even regulatory decisions have also become subject to judicial control by making them illegal. Furthermore, the supervisory powers of the Administrative Judge have also extended to the examination of the appropriateness of administrative conduct, which until recently was a red line For the administrative judge, it appeared so many judicial theories that allow and justify judicial control over the discretion of the management authority. Keywords: Administrative Judge, Judicial control, Legitimacy, Appropriate, Administration